A Study of Poverty and Consumption Inequality in India from years 2004-05 through the Pandemic Year (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The poor's improved standard of living must be the ultimate goal of economic expansion. The opposite of rapid and consistent poverty reduction is not just ineffective; it might make the situation worse. In a similar vein, if rapid development is accomplished by unequally distributing its benefits, it will not last. Indeed, it is conceivable to conceive a scenario where economic expansion exacerbates inequality to the point where poverty levels increase. Our research is the first to examine the long-term effects of in-kind food subsidies on poverty and inequality in India from 2004-2005 to the epidemic year. The low incidence of severe poverty in 2019 before the epidemic was maintained in large part due to food assistance.